Integrasi Nilai Tauhid dalam Kewirausahaan : Studi Kasus pada Bisnis Kerajinan Sapu Injuk - Padlan Padilah; Fujiah Zaharani; Syahrul Anwar (MES Bogor, 2025)
The application of the values of tauhid in entrepreneurship is an essential step in creating ethical and responsible business practices, particularly in a society with a Muslim majority, ensuring a balance between worldly interests and spiritual values. Furthermore, the integration of tauhid values can enhance public trust, which fosters the creation of sustainable and high-quality businesses. One example of this is the craft of sapu injuk, which carries local values and is oriented towards sustainability through the economic empowerment of the local community and the use of environmentally friendly raw materials. This study adopts a qualitative approach with a case study method, focusing on a broom-making entrepreneur in Kampung Muaradua, Desa Muaradua, Kadudampit District, Sukabumi Regency, West Java Province. Data were collected through in-depth interviews, field observations, and document analysis, aiming to explore the entrepreneur's perspectives and experiences in applying the values of Al-Tauhid in their business. The results of the study show that the entrepreneur implements Al-Tauhid principles by maintaining honesty in product quality, setting fair prices, and building respectful and responsible relationships with employees and business partners. Furthermore, they view their business as a form of worship, aiming not only for profit but also to bring blessings and provide social benefits to the surrounding community, especially through the empowerment of local labor. The application of Al-Tauhid values in this sapu injuk business has proven to have a positive impact, both in enhancing customer loyalty and in strengthening harmonious relationships with employees and the community. This study emphasizes that Al-Tauhid values can serve as a foundation for creating sustainable, ethical, and socially impactful businesses, encouraging Muslim entrepreneurs to prioritize spiritual values in their business practices in order to achieve blessings and long-term business success.